Aerobic resistance of Trichomonas vaginalis to metronidazole induced in vitro - Tachezy, J; Kulda, J; Tomková, E (Parasitology, 1993)
Aerobic resistance of Trichomonas vaginalis to metronidazole was induced in vitro by anaerobic cultivation of drug-susceptible trichomonads with low concentrations of the drug (2-3 micrograms/ml) for 50 days. Minimal lethal concentrations (MLC) for metronidazole of the resistant derivatives were high in aerobic susceptibility assays (MLC = 216-261.5 micrograms/ml) but low in anaerobic assays (MLC = 4.2-6.3 micrograms/ml), surpassing MLC values of their parent strain approximately 50-fold and 3-fold under aerobiosis and anaerobiosis, respectively. Sensitivity to metronidazole under anaerobic conditions and activity of the hydrogenosomal enzyme pyruvate: ferredoxin oxidoreductase indicated that the resistance was of the aerobic type. Dependence of the resistance manifestation on O2 was further confirmed by susceptibility assays in vitro performed in defined gas mixtures of different oxygen content (1-20%). Five percent concentration of O2 proved to be the threshold required for resistance demonstration and the MLC values further increased with increasing O2 concentrations. The in vitro-induced resistance was also demonstrated in vivo by subcutaneous mouse assay. The dose of metronidazole needed to cure 50% of infected mice (DC50) was 223 mg/kg x 3 for resistant derivative MR-3a but 6.6 mg/kg x 3 only for its drug-susceptible parent strain. The metronidazole-resistant strains developed in this study correspond by their properties to drug-resistant T. vaginalis strains isolated from patients refractory to treatment, and promise to be a useful tool in the study of 5-nitroimidazole aerobic resistance.
Keywords: Drug Resistance; Oxygen; Pyruvate Synthase; vztah mezi dávkou a účinkem léčiva; anaerobióza; Metronidazole; ketonoxidoreduktasy; léková rezistence; Trichomonas vaginalis; Animals; kyslík; metronidazol; Aerobiosis; zvířata; Anaerobiosis; pyruvátsynthasa; aerobióza; Dose-Response Relationship, Drug; Ketone Oxidoreductases